Accelerators and Colliders - Artun, Ozan (IntechOpen, 2020)
Since the mid-twentieth century, accelerators and colliders have been at the forefront of science and technology in the fields of space, medicine, energy, and others. This book presents sophisticated knowledge about accelerators and colliders and their crucial technological applications. With six chapters, the book presents information about currently available accelerators and colliders as well as novel schemes for future systems. Other topics covered include vacuum systems, elementary particles, and quantum chromodynamics.